Strategies For Improving Employee Performance at PT. PLN Manokwari: An Empirical Study - Budiman, Budiman; Mattalatta, Mattalatta; Gunawan, Gunawan; Hasmin, Hasmin (Devotion : Journal of Research and Community Service, 2025)
This study aims to analyze the Employee Performance Improvement Strategy of PT. PLN (Persero) Manokwari through the influence of knowledge management and employee empowerment on employee performance mediated by dynamic capabilities and job satisfaction. This study uses a quantitative approach. The sample of this study is all employees of PT PLN (Persero) Manokwari totaling 210 respondents. The research data was obtained from filling out questionnaires, analyzed using SEM-AMOS. The results of the study show that (1) Knowledge management and empowerment have a positive and significant effect on dynamic capabilities; (2) Knowledge management and empowerment have a positive and significant effect on job satisfaction; 3) Knowledge management does not have a significant effect on employee performance; 4) Empowerment has a positive and significant effect on employee performance; (5) Dynamic capabilities and job satisfaction have a positive and significant effect on employee performance; (6) Knowledge management and empowerment have a positive and significant effect on employee performance through dynamic capabilities,7) Knowledge management and empowerment have a positive and significant effect on employee performance through job satisfaction.